Assessing the development and treatment of rheumatoid arthritis using multiparametric photoacoustic and ultrasound imaging. Issue 11 (23rd July 2019) - Guo, Heng; Wang, Qin; Qi, Weizhi; Sun, Xun; Ke, Bowen; Xi, Lei
Abstract: Rheumatoid arthritis (RA), characterized by polyarthritis, is a chronic, systemic and inflammatory autoimmune disease. In this study, we developed a dual‐modality multiparametric photoacoustic and ultrasound imaging technique, and successfully derived multiple parameters such as relative concentration of total hemoglobin ( C HbT ), ratio of angiogenesis, joint size and area of synovia to assess the development and treatment of RA. We established a model of adjuvant arthritis using a total number of 15 rats and randomly divided them into three groups: (a) targeted group in which the rats received targeted antirheumatic drugs; (b) nontargeted group in which the rats were treated with nontargeted antirheumatic drugs; (c) control group. We longitudinally monitored the joints of the rats in all three groups for up to 20 days and carried out quantitative analysis to evaluate the development and treatment of RA based on the derived parameters. The results suggest that the proposed dual‐modality imaging technique is able to assess the effectiveness of the RA treatment using quantitative hemodynamic and morphological parameters. To show the clinical feasibility of this technique, we performed in vivo joint studies of health volunteers to visualize both structures and inside hemodynamics of the distal interphalangeal joint. Abstract : Rheumatoid arthritis (RA), characterized by polyarthritis, is a chronic, systemic and inflammatory autoimmune disease. Apart from the clinical evaluation standards, we assess the development of RA and the efficacy of the treatment noninvasively using both functional and morphological parameters derived by multiparametric dual‐modality photoacoustic and ultrasound imaging technique, which demonstrated the clinical feasibility of this technique in RA diagnosis and research.